A comparative assessment and medium term projections of redfish (S. mentella and S. fasciatus) in NAFO division 3M - Ávila de Melo, A.; Alpoim, R.; Saborido-Rey, Fran (Northwest Atlantic Fisheries Organization, 2001)
66 páginas, 19 tablas, 10 figuras.-- Scientific Council Meeting The present assessment evaluates the status of the 3M beaked redfish stock, regarded as a management unit composed of two populations from two very similar species (Sebastes mentella and Sebastes fasciatus). Survey bottom biomass and survey female spawning biomass were calculated based on the abundance at length from Canadian (1979-1985) and EU (1988-2000) bottom trawl surveys, and on the length weight relationships derived from EU survey data. The analytical assessment used a 1989-00 catch at age matrix starting at age 4 and incorporating the 1993-2000 redfish by-catch in the shrimp fishery at age. An Extended Survivor Analysis (Shepherd, 1999), including a 2000-1994 Retrospective Analysis, was first performed and complemented further by a Separable/Cohort analysis (Pope and Shepherd, 1982). Both models gave similar trends of stock biomass, spawning stock biomass and fishing mortality over the past twelve years. However the full weight of the former high catches of adult beaked redfish (greater than 30cm) on the SPA fit of the correspondent fishing mortalities lead to higher 1989-1993 F’s from the Cohort analysis and lower 1989-1998 SSB’s than those from XSA. A logistic surplus production model (ASPIC) which does not use the equilibrium assumption (Praguer, 1994 and 1995) was also applied using the 1959-2000 catch coupled with the STATLANT standardised CPUE series (1959-1993) and the age 4 plus EU bottom biomass (1988-2000). These last results, as regards biomass and fishing mortality trends are identical to the VPA based ones though with a faster rate of biomass increase over the final years of 1998-2000. Either VPA’s and ASPIC analysis pointed out that the 3M beaked redfish stock experienced a steep decline from the second half of the eighties till 1994-1996. Biomass is increasing since then but is still well bellow the level estimated by each model for the beginning of the time series (1989). Till 1996 fishing mortality was kept well above ...